Sosialisasi Nomor Induk Berusaha Sebagai Dasar Legalitas UMKM di Desa Padelengan Kecamatan Pademawu Pamekasan - Muhammad Januar Renaldi; Ikhlasul Abdillah; Yuliya Indriyana; Ferdy firmansyah (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This research aims to analyze the importance of the Business Identification Number (NIB) as the basis for the legality of Micro, Small and Medium Enterprises (MSMEs) in Padelengan Village, Pademawu District, Pamekasan Regency. This research was conducted using qualitative descriptive methods and a case study approach. Research data was collected through in-depth interviews with MSME owners in Padelengan Village, as well as through documentation studies related to regulations and policies regarding the provision of NIB to MSMEs. The research results show that NIB has a very important role in providing legality and legal protection for MSMEs in Padelengan Village. By having an NIB, MSMEs can gain easier access to various facilities and assistance from the government, and can run their business more safely and securely. However, this research also found several obstacles in providing NIB to MSMEs in Padelengan Village, including a lack of understanding and awareness of MSME owners about the importance of having an NIB, as well as a lack of access and information regarding NIB processing procedures. Based on the results of this research, it is recommended that the village government and related agencies carry out outreach and assistance to MSME owners to increase understanding and awareness of the importance of having an NIB. Apart from that, it is also necessary to improve access and information related to NIB processing procedures so that the process can run more effectively and efficiently. It is hoped that this research can contribute to improving legality and legal protection for MSMEs in Padelengan Village, as well as being a reference for further research related to the role of NIB in supporting the development of MSMEs in rural areas.